Usability an complement of perception on design elements for product label - Mohd Kamil, Mohd Hafiz Faizal; Jaafar, Azizah; Ahmad, I. (2011)
This study is focused on relationship between consumer and product label design. Usability aspect is one of the assessment factor to determine the effectiveness of a product label design to the consumer. However, consumer aspects such as awareness and trust should be given attention in order to obtain a positive impact for making an accurate and correct purchase decisions based on product label design.